UPAYA MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS MENGGUNAKAN MODEL PEMBELAJARAN PROBING-PROMPTING SISWA KELAS VIII SMP NEGERI 46 MERANGIN - Susanti, Ade (MAT-EDUKASIA, 2016)
Mathematics plays an important role in human life, so it requires an understanding of the mathematical concepts that are good for mathematical material. But in reality, students' understanding of mathematical concepts is still quite low. Based on the learning outcomes obtained by students there are still many who are below the minimum completeness criteria (KKM). Therefore, to overcome the existing problems, the probing-prompting learning model is used which will be able to improve the understanding of the mathematical concepts of class VIII students of SMP N 46 Merangin. The research method used was PTK. Subjects in the eighth grade students of SMP Negeri 46 Merangin 2014/2015 academic year were 19 students. Data is collected using technical written tests and observations of students during the learning process. Based on the results of the study, it was found that understanding the mathematical concepts of students experienced a fairly good improvement compared to before. This can be seen from the learning outcomes obtained by students each cycle. The average learning outcomes obtained by students are: cycle I of 62.37 with the number of students completed 4 people. Increased in cycle II to 78.95 with a total of 13 students completed. in the third cycle student learning outcomes increased to 14 people with an average value of 84.47.